2014
DOI: 10.5901/mjss.2014.v5n22p292
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Balance of Knowledge Workers In Poland

Abstract: The subject of managing both work and family spheres has drawn a lot of academic attention in the last few decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The requirement (and/or the need) to monitor and react to people's behaviors on-line might refer to the phenomenon of the fear of missing out (FoMO) -the need to follow what others are doing all the time [38,39]. Previous studies have revealed that FoMO directly re- Similarly, the work-related Internet use besides working hours has previously been evidenced to increase the risk of family problems [43]. As a result, the integration of work and private spheres, manifested in performing some family-related activities when at work and work-related tasks besides working hours is assumed to improve individual's work performance, while deteriorating family engagement or satisfaction [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement (and/or the need) to monitor and react to people's behaviors on-line might refer to the phenomenon of the fear of missing out (FoMO) -the need to follow what others are doing all the time [38,39]. Previous studies have revealed that FoMO directly re- Similarly, the work-related Internet use besides working hours has previously been evidenced to increase the risk of family problems [43]. As a result, the integration of work and private spheres, manifested in performing some family-related activities when at work and work-related tasks besides working hours is assumed to improve individual's work performance, while deteriorating family engagement or satisfaction [45].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, on-line workers may satisfy their need for social interactions via Internet contacts that, at least partially, could be realized also during working hours. Permanent access to the Internet and social media might enhance maintaining relationships with friends and work-related electronic communication besides working hours, the greater the perceived work-life conflict experienced by the studied workers [42], and the higher the risk of having family problems, such as issues related to marriage, children or elderly family members [43]. It is possible that the on-line workers whose work demands monitoring the Internet users' behaviors might experience the negative consequences of what is particularly apparent in their case -the issue of blurred boundaries between home and working time.…”
Section: Discussionmentioning
confidence: 99%